2020
DOI: 10.51870/cejiss.r140401
|View full text |Cite
|
Sign up to set email alerts
|

Rabia Akhtar: The Blind Eye, U.S. Non-Proliferation Policy Towards Pakistan From Ford to Clinton

Abstract: cejiss acts as a forum for advanced exploration of international and security studies. It is the mission of cejiss to provide its readers with valuable resources regarding the current state of international and European relations and security. To that end, cejiss pledges to publish articles of only the highest calibre and make them freely available to scholars and interested members of the public in both printed and electronic forms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 106 publications
0
1
0
Order By: Relevance
“…With the breakup of alliances in the 1970s the aid flow to Pakistan was also reduced as US only granted US$ 2.9 million military aid during 1972-79, and US$ 2.55 billion economic aid during the same period, which showed that Washington was interested in economic development of the state rather than a military collaboration. Washington was well aware of the Sino-Pakistan nuclear cooperation in 1983 (Bagchi, 2017), despite it, US turned blind eye on nuclear programme of Pakistan (Akhtar, 2018). US continued to provide aid that jumped to US$ 5 billion in the 1979-90 period in which Islamabad was engaged in a proxy war against the Soviet forces occupation of Afghanistan.…”
Section: Shift In Us Foreign Policymentioning
confidence: 99%
“…With the breakup of alliances in the 1970s the aid flow to Pakistan was also reduced as US only granted US$ 2.9 million military aid during 1972-79, and US$ 2.55 billion economic aid during the same period, which showed that Washington was interested in economic development of the state rather than a military collaboration. Washington was well aware of the Sino-Pakistan nuclear cooperation in 1983 (Bagchi, 2017), despite it, US turned blind eye on nuclear programme of Pakistan (Akhtar, 2018). US continued to provide aid that jumped to US$ 5 billion in the 1979-90 period in which Islamabad was engaged in a proxy war against the Soviet forces occupation of Afghanistan.…”
Section: Shift In Us Foreign Policymentioning
confidence: 99%